Case report: Multiple brain intravascular papillary endothelial hyperplasia: incidence, diagnostic challenges, and management approach - Anghileri, Elena; Pollo, Bianca; Ferroli, Paolo; Aquino, Domenico; Demichelis, Greta; Schiariti, Marco; Ferrau, Francesco; Chiapparini, Luisa; Cuccarini, Valeria (Frontiers in Neurology, 2023)
Multiple hemorrhagic brain lesions are mostly diagnosed by clinical-radiological features, eventually integrated to histological data. In such context, intravascular papillary endothelial hyperplasia (IPEH) or Masson’s tumor is a very rare entity, especially when exclusively localized in the brain. We describe the case of multiple recurrent brain IPEH, covering the diagnostic phase, the therapeutic approaches, and the related challenges. A 55-year-old woman experienced relapsing neurological deficits. Brain magnetic resonance imaging (MRI) showed hemorrhagic right frontal-parietal lesion. When new neurological signs later on occurred, further bleeding cerebral lesions were detected on subsequent MRIs. She underwent repetitive surgeries: the first histopathological examination resulted not informative (i.e. clot), the second and the third defined the case as hemangioendothelioma (HE) and the fourth concluded for the IPEH diagnosis. Systemic therapy was prescribed: initially interferon alfa (IFN-α) and later sirolimus, both well-tolerated. The clinical and radiological features are still stable after 43 months of sirolimus therapy initiation, and at 132 months from first diagnosis. To date, 46 intracranial IPEH have been reported, mostly as single lesion without parenchymal location, usually treated with surgery and sometimes by radiotherapy at recurrence. The case we report is impressive for two main reasons: first, because of the consecutive recurrent multifocal exclusively cerebral lesions over a very long period; second, for the therapeutical approach used. Based on multifocal brain recurrence and the good performance, we proposed pharmacological therapy, including IFN-α and sirolimus, resulting in the stabilization of disease.